Investigating human thumb models via their range of motion volumes - Phutane, Uday; Roller, Michael; Björkenstam, Staffan; Leyendecker, Sigrid (Proc. Appl. Math. Mech (PAMM), 2017)
The human thumb possesses joint axes with intricate descriptions, which enable the thumb to perform complex motions like opposition. To validate a thumb multibody model kinematically, we firstly study the difference in the volumes of the thumb tip workspace for the maximum range of motion (RoM) and the grasp RoM. We compare the volume difference for five models (with same joint designs but different axes locations and orientations) with data from literature. Secondly, we compute the rotation of the thumb along the longitudinal axis (internal rotation) for one joint for different postures. We compare the rotations for the five models with measured data from literature. In both checks, the results obtained from simulation are in close agreement with literature data and consequently the thumb model’s kinematics is validated.